La inutilizzabilità della prestazione - Pietro Peruzzi (Premio Tesi di Dottorato, 2017)
The service covered by an obligation corresponds, in the definition offered by the law (art. 1174 of the Italian civil code), to an interest of the creditor. What happens if this interest, in the context of a contractual relationship, can no longer be satisfied due to unforeseen causes not attributable to the parties? The jurisprudence affirms that when an interest is objectively functional and necessary for the realization of the contractual program, its infringement can lead to the cancellation of the legal bond. However, what are the exact legal consequences of such cancellation, and what are its forms? This is the essential content of this work, aimed at investigating the foundation and content of the extra-legislative category of the unexpected unusability of a service.